The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2215/cjn.05270515
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against Linear Epitopes of Myeloperoxidase in Anti–Glomerular Basement Membrane Disease

Abstract: Background and objectives Approximately 20%-30% of patients with anti-glomerular basement membrane disease present coexisting anti-myeloperoxidase (MPO) autoantibodies. We previously showed the recognition of a linear fragment of the MPO heavy chain N-terminus ( 1 H, MPO 279-409 ) in plasma from most double-positive patients. Herein, we investigated the frequency of autoantibodies against overlapping 1 H-derived linear peptides in plasma from patients with anti-glomerular basement membrane disease.Design, sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The recent observation that a high proportion of patients with anti-GBM disease have autoantibodies reactive to linear epitopes of MPO might support this hypothesis, as it suggests reactivity to conformational epitopes might arise as a consequence of inter- and intramolecular epitope spreading initiated by anti-GBM disease. 33 Whether additional environmental or genetic factors predispose to forming both antibodies is unclear. The genetic associations of both anti-GBM disease and AAV are increasingly well-described, 34 , 35 and both conditions have strong associations with certain HLA genes.…”
Section: Discussionmentioning
confidence: 99%
“…The recent observation that a high proportion of patients with anti-GBM disease have autoantibodies reactive to linear epitopes of MPO might support this hypothesis, as it suggests reactivity to conformational epitopes might arise as a consequence of inter- and intramolecular epitope spreading initiated by anti-GBM disease. 33 Whether additional environmental or genetic factors predispose to forming both antibodies is unclear. The genetic associations of both anti-GBM disease and AAV are increasingly well-described, 34 , 35 and both conditions have strong associations with certain HLA genes.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a recent study found that up to 60% of anti-GBM cases also had antibodies directed against linear epitopes of MPO, versus 24% recognizing intact MPO. The authors hypothesize that MPO-ANCA recognizing linear and conformational epitopes may arise sequentially, via a process of inter-and intramolecular epitope spreading (87). We recently analyzed the outcomes of a large cohort of these "doublepositive" patients from four centers in Europe, and found that they experience the early morbidity and mortality of anti-GBM disease, with severe kidney and lung disease at presentation, requiring aggressive immunosuppressive therapy and plasma exchange (88).…”
Section: Post-transplant Anti-gbm Disease In Alport Syndromementioning
confidence: 99%
“…Prior cases of double-positive disease have demonstrated that double-positive patients with MPO-ANCA positivity have worse prognosis than double-positive patients with PR3-ANCA positivity: the mortality of double-positive patients with MPO-ANCA and PR3-ANCA are 33% (18 of 55) and 22% (4 of 18), respectively. Of note, a recent study showed that the majority (63%, 42 of 67) of patients with anti-GBM disease are positive for autoantibodies against the linear fragment of the MPO heavy chain N-terminus, whereas only 24% (16 of 67) of them were positive for intact MPO [ 17 ]. Furthermore, several autoantibodies against the MPO linear fragment are associated with disease severity, including high serum creatinine levels and high probability of progression to end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%